BERTOLT BRECHT'S DEUTSCHLAND POEM WHICH DESCRIBES THE INHUMANITIES OF THE HITTLER ERA'S LEADERSHIP - Girsang, Martina; Damanik , Andrini Aurellia Anggi; Tambunan, Putri Yustika; Silitonga, Ruth Friska; Tamba, Septriyuni Rumondang (BASIS (Bahasa dan Sastra Inggris), 2023)
Poetry (Gedich) is a literary work that belongs to the category of lyrics. Compared to other types of literary works such as epics and dramas, poetry has a more dense and beautiful language and the meaning in poetry is multi-interpreted. Each individual can have their own interpretation. The language used in poetry is also not everyday language. Tells about the struggle of the German people during the Nazi occupation, and the sadness of the German people who live with great difficulties. So this poem explains the condition of Hitler’s leadership which did not put humanity first, so that many died in the end and it was the nation’s best sons who were sacrificed for war with the condition that all access was limited. The creation of meaning in Deutschland poetry is caused by rhyme and enjambement. The rhyme in the poem is irregular, this illustrates that what is characteristic of beauty is not prioritized, but emphasizes the integrity of meaning. Apart from rhyme, Enjambement is also found in poetry.Germany is also hated by other countries due to Hitler’s actions. Initially Hitler’s decision to annex Austria (15 March 1938) and Czechoslovakia was still tolerated by other nations, but then the dispossession of Poland had precipitated the outbreak of World War II.